2020
DOI: 10.3892/etm.2020.9529
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives on skin disorder diagnosis among people living with HIV in southeastern Romania

Abstract: The beginnings of the human immunodeficiency virus (HIV) pandemic are closely linked to dermatological conditions. A large part of the population living with HIV (PLWH) has a series of skin conditions that determine at some point, a visit to the dermatologist. The introduction of highly active antiretroviral therapy (HAART) more than 20 years ago has diminished the range of dermatological conditions, with improved immunosuppression of CD4 lymphocytes. The study aimed to describe the prevalence of the diagnosed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…The non-modifiable factors which are mainly incriminated in BCC development in the Caucasian population are the following: A fair skin (Fitzpatrick skin types I and II), a light eye color, blonde/red hair, freckles, photosensitizing medication (tetracyclins, hydrochlorothiazide and statins) and exposure to carcinogenic substances (such as arsenic). Along with other skin pathologies (Kaposi's sarcoma, herpes zoster, oral candidiasis or hairy leucoplakia), BCC has been observed to develop with a 2-and 5-fold increased frequency in patients who are human immunodeficiency virus (HIV)-positive and, respectively, in those who have received organ transplants (7,9,(13)(14)(15)(16)(17)(18).…”
Section: Pathogenesis and Risk Factorsmentioning
confidence: 99%
“…The non-modifiable factors which are mainly incriminated in BCC development in the Caucasian population are the following: A fair skin (Fitzpatrick skin types I and II), a light eye color, blonde/red hair, freckles, photosensitizing medication (tetracyclins, hydrochlorothiazide and statins) and exposure to carcinogenic substances (such as arsenic). Along with other skin pathologies (Kaposi's sarcoma, herpes zoster, oral candidiasis or hairy leucoplakia), BCC has been observed to develop with a 2-and 5-fold increased frequency in patients who are human immunodeficiency virus (HIV)-positive and, respectively, in those who have received organ transplants (7,9,(13)(14)(15)(16)(17)(18).…”
Section: Pathogenesis and Risk Factorsmentioning
confidence: 99%
“…34 Such challenges are present in the Romanian health system not only concerning MDR but also cancer diagnosis and treatment, associated high-risk diseases and treatment side effect risk, being major stressors not only for treating physicians but also for the patients, whom not rarely are of young age (such being the case of spiradenocarcinoma or AIDS (acquired immunodeficiency syndrome) patients) or can develop side effects even to commonly used drugs (such as betablockers); adequate treatment is thus an issue with consequent severe psychological impact. [40][41][42][43] ESKAPE AMR evaluated in this study is lower than other resistances reported nationally in invasive infections, but it reflects their prevalence and persistence within the community. Pursuit for superbug surveillance in the infectious diseases hospital must develop by increasing the quality and accuracy of the identifying methods used, by adopting the EUCAST standards, increasing the clinical vigilance for infectious diagnosis and justified use of antibiotics.…”
mentioning
confidence: 91%
“…On the contrary some studies reported as the frequency of HZ declined after ART (3). Herpes Zoster, along with extensive oral candidiasis, and oral hairy leukoplakia, as indicator of the acquired immunodeficiency syndrome (AIDS) (12).…”
Section: Discussionmentioning
confidence: 99%